2020
DOI: 10.1161/strokeaha.120.030794
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke Management During the COVID-19 Pandemic

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, the World Health Organization recommended measures to mitigate the outbreak such as social distancing and confinement. Since these measures have been put in place, anecdotal reports describe a decrease in the number of endovascular therapy (EVT) treatments for acute ischemic stroke due to large vessel occlusion. The purpose of our study was to determine the effect on EVT for patients with acute ischemic stroke during the COVID-19 confinement. In this ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 12 publications
5
20
2
Order By: Relevance
“…During the pandemic, one major negative impact on acute care for stroke was the decline in emergency hospital admissions, consistent with reports in different regions in China or other countries. The degree of reduction varied from 10 to 70% (11,13,13,(16)(17)(18)(19)(26)(27)(28)(29)(30)(31). One recent report in China also reported a 40% reduction in stroke hospital admissions (16), similar to our results (45.6%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…During the pandemic, one major negative impact on acute care for stroke was the decline in emergency hospital admissions, consistent with reports in different regions in China or other countries. The degree of reduction varied from 10 to 70% (11,13,13,(16)(17)(18)(19)(26)(27)(28)(29)(30)(31). One recent report in China also reported a 40% reduction in stroke hospital admissions (16), similar to our results (45.6%).…”
Section: Discussionsupporting
confidence: 89%
“…Our study also examined the question whether there was a delay in emergency care for AIS. In the previous reports, significant delays happened in prehospital stage (14,34), but whether there were delays in workflow metrics during the acute care was conflict (13,14,26,28). According to our results, in the prehospital stage, the OTD time became shorter in the lockdown period, which may benefit from the better traffic situation.…”
Section: Discussionsupporting
confidence: 50%
“…However, this difference was not significant when patients underwent thrombectomy at the first hospital that they presented to [7]. A study of 17 thrombectomy centres in Europe, Canada and the USA showed a significant decrease in the number of thrombectomies performed and an increase in stroke onset-to groin puncture after confinement measures were put in place [14].…”
Section: Discussionmentioning
confidence: 99%
“…As people continue to adjust to social distancing, a shift in the epidemiology of stroke and other medical conditions will most likely be observed, as is being seen in myocardial infarction [29] and in other countries [30][31][32][33][34][35][36][37] in the context of acute ischemic stroke. Although there is evidence to suggest a high rate of cerebrovascular complications in patients with SARS-CoV-2 infection [38][39][40][41][42][43], anecdotal reports indicate a falling rate of new ischemic stroke admissions [30][31][32]34,37,[44][45][46][47][48], stroke code activations [30,36,[49][50][51][52][53], imaging numbers [44,45], and diagnoses [45].…”
Section: Decrease In Ischemic Stroke Patientsmentioning
confidence: 99%
“…Additionally, decreases in acute ischemic stroke treatment numbers have been noted for both thrombolysis [46,53,56,57] and EVT [30,33,47,53,56], with an excellent meta-analysis presented by July et al [53], including data from nine studies [30,56,[58][59][60][61][62][63][64]. Details of each of these studies, as well as other related studies [65,66], can be found in Table S2 (Multimedia Appendix 1).…”
Section: Decrease In Ischemic Stroke Patientsmentioning
confidence: 99%